Significance of Lewy Body Formation in Development of Parkinson’s Disease - Sahay, Shivanki; Sutiono, Dias Rima (PT. Kalbe Farma Tbk., 2018)
Parkinsonâ€™s disease is a serious neurodegenerative disease characterized by depletion of neurons in the substantia nigra of the basal ganglia. These dying out neurons are found to contain traces of Lewy bodies, an abnormal protein filament of alpha-synuclein and that otherwise play an important role in the nervous system, especially at synapses.Penyakit Parkinson merupakan penyakit neurodegeneratif serius ditandai dengan deplesi neuron di substansia nigra ganglia basalis.Neuron ditemukan mengandung jejak Lewy Bodies, yang merupakan filamen protein abnormal alpha-synuclein.Â